Pemikiran Pembaharuan Jamaluddin Al-Afghani: Studi Pemikiran Kalam tentang Takdir - Noorthaibah, Noorthaibah (FENOMENA, 2015)
The epistemology paradigm of Islamic thoughts is developed from one era to another. This paper tries to reveal the modern Islamic thoughts proposed by Jamaluddin Al-Afghani in reconstructing the understanding of qadha and qadar (takdir) from fatalistic and statis thoughts into dynamic thoughts. The meaning of fana and baqa in sufism, according to Al-Afghaniâs thought, is real. The faith does not mean avoiding the needs of real life, but it should empower the social welfare and improve the social life. Al-Afghani states that the confession of the faith (qadha and qadar) is one of the basic elements in theology which cannot be avoided, yet it should be understood correctly and positively to reach the happiness in this world and the life after death.